Estimating the effects of entry regulation in the Istanbul taxicab market - Cetin, Tamer; Eryigit, Kadir Yasin (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The economic literature shows that entry regulation in taxicab markets brings about a dramatic increase in medallion prices or license values of taxicabs. However, there is no study estimating what the effect of regulation is exactly on real medallion prices. We develop a model to estimate the effect of entry restrictions in the Istanbul taxicab market over real medallion prices and inflation. Our findings contribute that entry regulation in taxicab markets increases medallion prices. Moreover, we find that entry regulation in Istanbul pressures inflation rates as well. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Economic regulation; Taxicab markets; Cointegration; Structural breaks; ECONOMIC REASONS; UNIT-ROOT; DEREGULATION; PRICE; COMPETITION; Business & Economics; Transportation